The economic cost of subway congestion: Estimates from Paris. (June 2018) - Haywood, Luke; Koning, Martin; Prud'homme, Remy
Abstract: Related to the increased encouragement of public transport (PT) by policy-makers, over-crowding in PT has become a major issue worldwide. Whilst the impact of in-vehicle crowding on individuals' travel costs has been considered, we focus on aggregate welfare losses. We apply a Pigouvian framework to the case of subways and compute the economic cost of congestion ( E C C ). We combine data of the 14 metro services of the Paris network with survey data from a contingent valuation study of in-vehicle congestion. The gap between current and optimal PT patronage is 9%, and E C C is moderate. For the entire Paris subway network our benchmark estimate of 64.6 million euros per year amounts to 0.9% of total users' costs. We also propose marginal congestion costs relevant for socioeconomic appraisals of transport projects. Highlights: We calculate aggregate welfare losses due to overcrowding on public transport (PT) in Paris. We find optimal PT patronage is 9% below current levels. Costs due to overcrowding are 0.9% of total user costs – small, but similar to car congestion costs in major cities. We differentiate costs by the 14 services of the Paris Metro. We propose various sensitivity tests for these results.